1993
DOI: 10.1111/j.1432-1033.1993.tb17583.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 13C and 1H Fermi contact shifts in horse cytochrome c The origin of the anti‐Curie effect

Abstract: Many ferricytochromes c exhibit a peculiar effect in which the 'H chemical shifts of the haem methyl groups appear in pairs and, although the paramagnetic shifts of the two groups with the larger shifts decrease with temperature, those of the pair with the smaller shifts actually increase. Recent NMR studies [Santos, H. and Turner, D. L. (1992) Eur. J. Biochem. 206, 721 -7281 gave ' H and I3C assignments for most of the haem substituents and the axial ligands in horse cytochrome c at 30°C and 50°C in both oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
73
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 42 publications
2
73
2
Order By: Relevance
“…The small chemical-shift range found for the haem resonances (the most shifted haem resonance appears at about 18 ppm and the chemical-shift span of the methyl group resonances is only 9 ppm), is indicative of a relatively high symmetry for the electron-spin distribution. This is supported by the fact that the 2-methyl group and the 12-methyl group show only very slight anti-Curie effects [32]. Furthermore, both the axial histidines experience reasonably large hyperfine shifts, suggesting roughly similar interactions with the haem iron, in contrast to ferricytochrome b5, the only other bis-histidinyl haem protein for which the haem electronic structure has so far been published [33].…”
Section: Discussionmentioning
confidence: 90%
“…The small chemical-shift range found for the haem resonances (the most shifted haem resonance appears at about 18 ppm and the chemical-shift span of the methyl group resonances is only 9 ppm), is indicative of a relatively high symmetry for the electron-spin distribution. This is supported by the fact that the 2-methyl group and the 12-methyl group show only very slight anti-Curie effects [32]. Furthermore, both the axial histidines experience reasonably large hyperfine shifts, suggesting roughly similar interactions with the haem iron, in contrast to ferricytochrome b5, the only other bis-histidinyl haem protein for which the haem electronic structure has so far been published [33].…”
Section: Discussionmentioning
confidence: 90%
“…The temperature dependence of the heme methyl shifts reveals that the 1-CH 3 , 5-CH 3 exhibit positive slopes that are steeper than Curie (T Ϫ1 ) behavior, whereas the 3-CH 3 , 5-CH 3 exhibit slopes that are negative or exhibits antiCurie behavior. This effect is expected on the basis of thermal population of the excited orbital state, where the lone spin on the iron becomes delocalized into pyrroles B and D (60,(67)(68)(69). Lastly, the magnetic axes reported above allow the determination of ␦ dip for the axial His, which, in turn, provides ␦ con for each of the positions, as shown in Table I.…”
Section: Discussionmentioning
confidence: 91%
“…In recent studies of ferricytochroine c3 from DvH, the "C resonances of the haem substituents were also identified . These assignments formed the basis for the elaboration of a theoretical model which describes the Fermi contact shifts of those carbon nuclei in terms of a molecular orbital of eg symmetry with a rhombic perturbation (Turner, 1993(Turner, , 1995Turner et al, 1995). Moreover, the study has shown that the Fermi contact shifts are directly related to the orientations of both axial ligands and hence that the axial ligands dominate the rhombic perturbation.…”
mentioning
confidence: 99%